Effect of termite activity on soil chemical properties using baiting systems at an arboretum area in Pontianak, West Kalimantan, Indonesia - Yuliati Indrayani; SOFWAN ANWARI (Society for Indonesian Biodiversity, 2021)
Abstract. Indrayani Y, Anwari S. 2021. Effect of termite activity on soil chemical properties using baiting systems at an arboretum area in Pontianak, West Kalimantan, Indonesia. Biodiversitas 22: 2125-2130. Termites play an essential and positive role as decomposers in nature, apart from being known as wood-destroying insects. These two varying characteristics led to the development of termite control technology, capable of digesting cellulose components and making soils rich in organic compounds. Therefore, this study examines the soil's biogenic structure due to termite activity using a control technology with a baiting system. The bait was made with various compositions of eucalyptus leaves, paper and cardboard, 60%: 40%: 0%, 60%: 20%: 20%, 60%: 0%: 40%, 0%: 100%: 0% and 0%: 0%: 100% with a size of 2cm x 2cm x 1cm and eucalyptus leaves as an attractant. In addition, a PVC tube measuring 10 cm diameter and 20 cm height with 25 holes consisting of 3 mm diameter on the side was used for field application. A total of 100 grams of bait for each composition was entered into the feed tube and placed in the Arboretum of Tanjungpura University, West Kalimantan, with three replications and left for 21 days. At the end of the observation period, the soil’s biogenic structures with termites were analyzed to determine their chemical properties. Furthermore, the same analysis was also carried out on the soil surrounding the test area without termite activity for comparison. The results showed that the pH, C/N ratio, C-Organic, Nitrogen, Phosphorus, and Potassium contents as well as Cation Exchange Capacity of the soil produced from the tube containing the bait with a composition of 60%: 0%: 40% was significantly higher. This means that the soil's biogenic structure produced by termite activity with a baiting system increases land productivity and chemical properties.